2019
DOI: 10.3390/nu11102381
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Fruits and Vegetables with Major Cardiometabolic Risk Factors, Markers of Oxidation, and Inflammation

Abstract: Noncommunicable diseases (NCDs) are considered to be the leading cause of death worldwide. Inadequate fruit and vegetable intake have been recognized as a risk factor for almost all NCDs (type 2 diabetes mellitus, cancer, and cardiovascular and neurodegenerative diseases). The main aim of this review is to examine the possible protective effect that fruit and vegetable consumption or their bioactive compounds may have on the development of NCDs such as atherosclerosis. The accumulated evidence on the protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 196 publications
(290 reference statements)
0
43
0
2
Order By: Relevance
“…As expected, levels of PUFA were higher in vegans compared to omnivores, and corresponding higher plasma PUFA concentrations were inversely correlated with hsCRP concentration. Moreover, also intake of fruit and vegetables has been suggested to attenuation inflammation indicated by a large body of scientific evidence 23,24 . At the level of bioactive compounds occurring in fruits and vegetables, primarily carotenoids and flavonoids seem to modulate inflammatory as well as immunological processes 23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, levels of PUFA were higher in vegans compared to omnivores, and corresponding higher plasma PUFA concentrations were inversely correlated with hsCRP concentration. Moreover, also intake of fruit and vegetables has been suggested to attenuation inflammation indicated by a large body of scientific evidence 23,24 . At the level of bioactive compounds occurring in fruits and vegetables, primarily carotenoids and flavonoids seem to modulate inflammatory as well as immunological processes 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, also intake of fruit and vegetables has been suggested to attenuation inflammation indicated by a large body of scientific evidence 23,24 . At the level of bioactive compounds occurring in fruits and vegetables, primarily carotenoids and flavonoids seem to modulate inflammatory as well as immunological processes 23,24 . Nevertheless, the present study detected no correlation between consumption of fruits and vegetables and inflammatory biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fruits are a source of carbohydrate that can fulfill the promotion of cellular and systemic damage and the deficit of glycogen faced post high intensity exercise (MCLEAY et al, 2012). The fruits may be composed of potassium, vitamin B6, C, E, pro-vitamins A phenolics, carotenoids, lutein, folic acid, magnesium, catecholamines, and antioxidants; all important in reduction of oxidative stress, inflammation, and recovery post high intensity exercise (NIEMAN et al, 2018a;LAPUENTE et al, 2019). Thus, fruits may assist in decreasing the effects of exercise on the body due to their anti-inflammatory and antioxidant capabilities.…”
Section: Fruits As Dietary Supplements For Exercise Recoverymentioning
confidence: 99%
“…In recent years, flavonoids have received a great deal of attention from specialists for the variety of potential benefits they offer. It is a complex and long-term study due to the heterogeneity of molecular structures, but numerous studies have suggested that dietary polyphenols may be beneficial as adjunctive treatment for the prevention and treatment of chronic inflammatory diseases [ 22 , 23 ]. Even though nowadays there are many plants known to possess a high concentration of flavonoids, maybe the best known are the vegetables and fruits extensively used as daily food.…”
Section: Introductionmentioning
confidence: 99%
“…Even though nowadays there are many plants known to possess a high concentration of flavonoids, maybe the best known are the vegetables and fruits extensively used as daily food. The table below presents a series of beneficial effects and composition of foods rich in flavonoids ( Table 2 ) [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%